2007
DOI: 10.1093/her/cym031
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of a multi-institutional community-based program for diabetes prevention among First Nations

Abstract: Epidemic rates of diabetes among Native North Americans demand novel solutions. Zhiiwaapenewin Akino'maagewin: Teaching to Prevent Diabetes was a community-based diabetes prevention program based in schools, food stores and health offices in seven First Nations in northwestern Ontario, Canada. Program interventions in these three institutions included implementation of Grades 3 and 4 healthy lifestyles curricula; stocking and labeling of healthier foods and healthy recipes cooking demonstrations and taste test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(140 citation statements)
references
References 43 publications
7
131
1
1
Order By: Relevance
“…Those respondents who were part of the intervention group or more exposed to the intervention were much more likely to purchase shelf label-promoted healthy foods. This finding is in line with much of our previous research on the utility and effectiveness of shelf labels as means of promoting healthier foods in retail food stores (23)(24)(25).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Those respondents who were part of the intervention group or more exposed to the intervention were much more likely to purchase shelf label-promoted healthy foods. This finding is in line with much of our previous research on the utility and effectiveness of shelf labels as means of promoting healthier foods in retail food stores (23)(24)(25).…”
Section: Discussionsupporting
confidence: 90%
“…The fact that we saw an impact on psychosocial and behavioral factors provides additional support for the validity of our associations. We have conducted food storecentered trials in other settings with indigenous peoples that have shown positive impacts on psychosocial factors and foodrelated behaviors (23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De gevonden implementatiegraad (52 %) is relatief hoog. Hoewel meer onderzoeken naar de implementatie van een integrale aanpak een dergelijke implementatiegraad rapporteren [18,19], is een compleetheid van meer dan 50 % ongebruikelijk hoog te noemen [20]. Daarnaast werd een positief verband gevonden tussen de mate van ervaring met implementatie en de compleetheid van implementatie.…”
Section: Beschouwingunclassified
“…Subtypes include media campaigns that combine mass media messages (e.g., series of exhibitions, lectures or ads on the reduction of alcohol consumption or smoking in adolescents (Bonfadelli and Friemel 2006). Another subtype involves the social development of a broad alliance of health care and political actors for concerted promotion of health awareness on different issues, such as rapid and highquality care for stroke victims through many channels, in many cases, with supportive media campaigns (Hannon et al 2009;Rosecrans et al 2008;Scheier and Grenard 2010). (structural, environmental): involve sociopolitical action aimed at changing risk behavior opportunities and decreasing the accessibility and costeffectiveness of risk substances by measures such as raising taxes, banning advertising and/or restricting access to cigarettes or alcohol and installing water coolers in schools.…”
Section: Introduction: Program Types and Objectivesmentioning
confidence: 99%